Reactive Eccrine Syringofibroadenoma (ESFA) in Association With a Merkel Cell Carcinoma Excision Scar. (19th February 2023) - Salah, Haneen T.; Czelusta, Adam J.; Sanchez, Ramon L.
Abstract: Eccrine syringofibroadenoma (ESFA) is a rare benign skin adnexal lesion of the acrosyringium of eccrine sweat ducts. Reactive ESFA, a subtype of ESFA, is usually associated with non-neoplastic cutaneous dermatoses or neoplastic skin tumors. Clinically, the lesions can be solitary or multiple, pink, or skin-colored coalescing papules or nodules of variable sizes. Histopathologically, this tumor is composed of numerous anastomosing cords of monomorphic cuboidal epithelial cells with eccrine duct formation. The association of reactive ESFA with benign conditions, such as psoriasis, diabetic polyneuropathy, scars, and leprosy, has been reported. However, the association of reactive ESFA with malignant tumors is extremely rare, with very few cases reported in the literature. We present a case of a 72-year-old woman who developed reactive ESFA associated with Merkel cell carcinoma excision scar. The ESFA tumors developed in the area of the surgical graft 10 months after the Merkel cell carcinoma had been excised. New ESFA tumors have continued to appear in the scar on a yearly basis while, so far, has been no recurrence of the original tumor. However, the presence of new tumor growths in the area suggested the possibility of recurrence of the Merkel cell carcinoma. That possibility was enhanced by the fact that PET scans revealed hypermetabolic activity in the ESFA papules.